Rivalry Onset in and around the Fovea: The Role of Visual Field Location and Eye Dominance on Perceptual Dominance Bias - Stanley, Jody (Vision (Basel), 2019)
When dissimilar images are presented to each eye, the images will alternate every few seconds in a phenomenon known as binocular rivalry. Recent research has found evidence of a bias towards one image at the initial ‘onset’ period of rivalry that varies across the peripheral visual field. To determine the role that visual field location plays in and around the fovea at onset, trained observers were presented small orthogonal achromatic grating patches at various locations across the central 3° of visual space for 1-s and 60-s intervals. Results reveal stronger bias at onset than during continuous rivalry, and evidence of temporal hemifield dominance across observers, however, the nature of the hemifield effects differed between individuals and interacted with overall eye dominance. Despite using small grating patches, a high proportion of mixed percept was still reported, with more mixed percept at onset along the vertical midline, in general, and in increasing proportions with eccentricity in the lateral hemifields. Results show that even within the foveal range, onset rivalry bias varies across visual space, and differs in degree and sensitivity to biases in average dominance over continuous viewing.